Zirconium-Based Ceramic Precursor Material for Polymer Infiltration and Pyrolysis Process, Method for Preparing the Same, and Method for Manufacturing Composite Ceramic Article Using the Same
Patent Information
- Application Number
- KR1020260062028
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-14
- Filing Date
- 2026-04-06
- Publication Date
- 2026-10-21
Smart Images

Figure PAT00015_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a zirconium-based ceramic precursor material, a method for manufacturing the same, and a method for manufacturing a composite ceramic molded body using the same. More specifically, the invention relates to a low-viscosity liquid zirconium-based ceramic precursor material comprising a polyzirconium compound, a method for manufacturing the same, and a method for manufacturing a high-density composite ceramic molded body using the same. Background Technology
[0002] With the advancement of the aerospace industry, the demand for materials usable in extreme environments is continuously increasing. In this regard, Ultra-High Temperature Ceramics (UHTCs) are attracting attention as promising candidate materials. In particular, zirconium-based ceramics are receiving attention for their excellent properties, such as high fracture toughness, wear resistance, high melting point, hardness, and heat resistance.
[0003] Zirconia (ZrO2) and zirconium carbide (ZrC) are representative zirconium-based ceramics with high melting points of 2715°C and 3532°C, respectively, which allow them to be used in extreme conditions involving high heat flux. However, due to these high melting points, they have low sinterability, making molding and sintering difficult, which is a limiting factor in their actual applications.
[0004] The Polymer Infiltration and Pyrolysis (PIP) process is one of the well-established methods for densifying and molding ultra-high temperature ceramics. This process involves infiltrating a low-viscosity polymer precursor into a porous matrix and then converting the precursor into a ceramic through high-temperature pyrolysis.
[0005] The PIP process offers the advantages of lower cost, shorter manufacturing time, and deeper penetration depth compared to the Chemical Vapor Infiltration (CVI) process. Additionally, the PIP process generally maintains a thermal decomposition temperature below 1600°C, which is lower than the temperature used in the Reactive Melt Infiltration (RMI) process. Due to these characteristics, the PIP process provides the possibility to manufacture ceramic parts with complex shapes in a near-net-shape.
[0006] However, the PIP process has limitations such as shrinkage and crack formation during pyrolysis. Therefore, the physical properties of the precursor become a key factor in determining the success of the PIP process.
[0007] Ceramic precursors are generally inorganic polymers containing metal atoms that can be converted into metal carbides, borides, or nitrides at high temperatures. For efficient matrix penetration, the precursor must be primarily in a liquid state or easily soluble in a solvent. For an optimal PIP process, low viscosity to facilitate penetration and high yield after pyrolysis must be satisfied simultaneously.
[0008] Metal carbide precursors can be classified into oxide precursors and non-oxide precursors.
[0009] Non-oxide precursors offer high ceramic yields after pyrolysis by avoiding additional mass loss associated with carbon thermal reduction. However, the high cost of starting materials, demanding reaction conditions, and the risk of explosion due to rapid oxidation limit their widespread application. In contrast, oxide precursors are more industrially applicable due to their ease of handling and lower cost. However, they have the disadvantage of slightly lower yields compared to non-oxide precursors.
[0010] Oxide precursors for zirconium-based ceramics are generally synthesized via a sol-gel reaction using zirconium alkoxides and carbon sources containing hydroxyl groups. However, this method has the following two major problems:
[0011] First, it is difficult to control the extent of the sol-gel reaction, often leading to an excessive increase in molecular weight and the formation of solid precursors. Applying these solid precursors to the PIP process requires additional solvents, which reduces yield and complicates the process. To overcome this, attempts have been made to maintain the precursors in a liquid state using chelating agents; however, optimizing reaction conditions remains challenging due to the varying reactivity of zirconium alkoxides and carbon sources.
[0012] Second, the oxygen content of the carbon and zirconium sources is high. 1500 during ZrC production As described above, oxygen must be removed through carbon thermal reduction. However, a high concentration of hydroxyl groups in the carbon source increases the carbon demand for oxygen removal, thereby reducing the yield. Additionally, there is a risk of matrix damage due to the generation of large amounts of CO2 and CO2 gases.
[0013] Additionally, conventional precursors often have high viscosity, which limits penetration into the matrix during the PIP process. Adding a solvent to address this leads to additional mass loss during the solvent removal process, further reducing the final ceramic yield.
[0014] Therefore, for an efficient PIP process, there is an urgent need to develop new zirconium-based ceramic precursors that simultaneously satisfy low viscosity, liquid state, low oxygen content, and high ceramic yield. The problem to be solved
[0015] The present invention has been devised to solve the problems of the prior art described above. One objective of the present invention is to provide a zirconium-based ceramic precursor material that maintains a liquid state at room temperature while having low viscosity characteristics, can be directly applied to the PIP process without the use of a solvent, and exhibits a high ceramic yield.
[0016] Another objective of the present invention is to provide a method for manufacturing the zirconium-based ceramic precursor material.
[0017] Another objective of the present invention is to provide a method for manufacturing a composite ceramic molded body using the zirconium-based ceramic precursor material. means of solving the problem
[0018] A zirconium-based ceramic precursor material according to an embodiment of the present invention may include a polyzirconium compound having a chemical structure of the following chemical formula 1, which is in a liquid state at room temperature, as a zirconium oxide precursor material.
[0019] [Chemical Formula 1]
[0020]
[0021] In the above chemical formula 1, R is a straight-chain or branched alkyl group having 2 to 4 carbon atoms, and n is an integer from 1 to 1000.
[0022] In one practical example, the -OR may be any one selected from the group consisting of an ethoxide group, an n-propoxide group, and an n-butoxide group. For example, the -OR may be an n-propoxide group.
[0023] In one actual example, the viscosity of the polyzirconium compound at 25°C may be about 470 to 570 cP.
[0024] In one exemplary embodiment, when heat-treated at 1300°C, the ceramic yield of the polyzirconium compound may be 50 to 55%.
[0025] A method for manufacturing a zirconium-based ceramic precursor material according to an embodiment of the present invention may include: a step of producing an intermediate product of formula b through a hydrolysis reaction between a zirconium alkoxide compound of formula a and acrylic acid according to the following reaction scheme 1; and a step of synthesizing a polyzirconium compound of formula 1 through a condensation reaction of the intermediate products.
[0026] [Reaction Equation 1]
[0027]
[0028] In the above reaction scheme 1, R is a straight-chain or branched alkyl group having 2 to 4 carbon atoms, and n is an integer from 1 to 1000.
[0029] In one embodiment, in the above reaction scheme 1, -OR may be any one selected from the group consisting of an ethoxide group, an n-propoxide group, and an n-butoxide group. For example, the zirconium alkoxide compound may include zirconium propoxide.
[0030] In one embodiment, the zirconium alkoxide compound and the acrylic acid can react in a molar ratio of 1:1.8 to 1:2.2.
[0031] In one embodiment, in the first step, some of the alkoxide groups of the zirconium alkoxide compound are substituted with a ligand derived from the acrylic acid, and some may remain.
[0032] A method for manufacturing a composite ceramic molded body according to an exemplary embodiment of the present invention may include: a first step of preparing a porous ceramic molded body; a second step of infiltrating a polyzirconium compound of the following chemical formula 1 and a radical initiator into the pores of the ceramic molded body; a third step of crosslinking the polyzirconium compound through polymerization between vinyl groups using the radical initiator; and a fourth step of converting the crosslinked polyzirconium compound into zirconium oxide by thermal decomposition.
[0033] [Chemical Formula 1]
[0034]
[0035] In the above chemical formula 1, R is a straight-chain or branched alkyl group having 2 to 4 carbon atoms, and n is an integer from 1 to 1000.
[0036] In one embodiment, the ceramic molded body may be formed of ZrB2, ZrC, or HfC.
[0037] In one embodiment, the crosslinking of the polyzirconium compound can be performed at 70 to 100°C.
[0038] In one embodiment, the thermal decomposition of the cross-linked polyzirconium compound can be performed at a temperature of 550°C or higher and 1400°C or lower. Effects of the invention
[0039] According to the zirconium-based ceramic precursor material, the method for manufacturing the same, and the method for manufacturing a composite ceramic molded body using the same according to an embodiment of the present invention, the polyzirconium compound maintains a liquid state at room temperature, thereby ensuring excellent penetration in the PIP process without adding a separate solvent, and accordingly, can prevent yield loss due to solvent removal and simplify the process.
[0040] In addition, the above polyzirconium compound can be cured at low temperatures through a double crosslinking mechanism using hydroxyl and vinyl groups, and as a result, can provide improved ceramic yield characteristics. Brief explanation of the drawing
[0041] FIG. 1 is a schematic diagram illustrating the entire manufacturing process including (a) synthesis of a ZrO2 precursor, (b) double crosslinking of the ZrO2 precursor, and (c) thermal decomposition of the hardened ZrO2 precursor. Figure 2 shows photographs of PZC samples before (a), after (b), and after (c) the reaction of Zr(OPr)4 with acrylic acid. Figure 3 shows the FT-IR spectra of the reactant, the liquid precursor (PZC-12), and the hardened precursor (c-PZC-12). Figure 4 is for a more detailed analysis of the molecular structure of PZC-12 1 H and 13 This is the result of the C NMR analysis. Figure 5 shows photographs and XRD patterns of ZrO2 powder obtained by pyrolysis at different temperatures. Figure 6 shows images of the microstructure of ZrO2 powder as a function of pyrolysis temperature observed using SEM. Figure 7 shows the TGA-DSC analysis results for the synthesized PZC-12 precursor. FIG. 8 is a diagram illustrating the processes for manufacturing a PIP process-based ZrB2-ZrO2 composite using a porous ZrB2 molded body. Figure 9 shows the density profile of the ZrB2-ZrO2 composite after each step of the PIP process (a), and the XRD patterns of the ZrB2-ZrO2 composite before and after three cycles of PIP. Specific details for implementing the invention
[0042] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings. Since the present invention is susceptible to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in the text. However, this is not intended to limit the present invention to the specific disclosed forms, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the present invention. Similar reference numerals have been used for similar components in the description of each drawing. In the attached drawings, the dimensions of the structures are shown enlarged compared to the actual dimensions for the clarity of the present invention.
[0043] Terms such as "first," "second," etc., may be used to describe various components, but said components should not be limited by said terms. These terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component.
[0044] The terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as "comprising" or "having" are intended to indicate the presence of the features, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, steps, actions, components, parts, or combinations thereof.
[0045] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0047] Zirconium-based ceramic precursor materials
[0048] A zirconium-based ceramic precursor material according to one embodiment of the present invention may include a polyzirconium compound that is in a liquid state at room temperature and comprises a repeating unit of the following chemical formula 1, as a precursor material of zirconium oxide.
[0049] [Chemical Formula 1]
[0050]
[0051] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000.
[0052] In one embodiment, in the case of the polyzirconium compound, the central metal zirconium (Zr) atom may bond with a plurality of oxygen atoms through coordination bonds to form an octahedral or tetrahedral coordination structure.
[0053] In one embodiment, for a suitable viscosity of the polyzirconium compound, n in Formula 1 may be an integer of about 1 to 1000, about 1 to 500, about 1 to 100, or about 1 to 50.
[0054] In one embodiment, in Formula 1, R represents a straight-chain or branched alkyl group having about 1 to 6 carbon atoms or about 2 to 4 carbon atoms. In one embodiment, R may be selected from the group consisting of ethyl (-C2H5), n-propyl (-C3H7), isopropyl (-CH(CH3)2), n-butyl (-C4H9), sec-butyl (-CH(CH3)C2H5), isobutyl (-CH2CH(CH3)2), tert-butyl (-C(CH3)3), etc. For example, R may be an n-propyl group.
[0055] In one embodiment, in Formula 1, the alkyl group having about 1 to 6 carbon atoms may serve to ensure liquid phase stability of the precursor by providing appropriate hydrophobicity and steric hindrance. If the number of carbon atoms is less than 1 (e.g., methyl group), steric hindrance is insufficient and premature gelation may occur, and if the number of carbon atoms is greater than 6, the condensation reaction may be excessively inhibited due to excessive hydrophobicity, resulting in insufficient molecular weight growth.
[0056] In one embodiment, the -OR group is derived from a zirconium alkoxide compound, and some of it is substituted with a carboxyl group during the reaction with acrylic acid, while some remains to form the structure of Formula 1. In one embodiment, the -OR can be selected from the group consisting of an ethoxide group, an n-propoxide group, an n-butoxide group, etc., and preferably, it can be an n-propoxide group.
[0057] In one embodiment, in Formula 1, n is an integer representing the degree of polymerization of the polyzirconium compound. The degree of polymerization n directly affects physical properties such as the molecular weight, viscosity, and ceramic yield of the precursor. In one embodiment, n may be in the range of about 1 to 1000. For example, n may be in the range of about 1 to 100 or about 1 to 50. If the degree of polymerization (n) is less than M1, the molecular weight is excessively low, which may increase volatilization loss during the curing process and reduce the ceramic yield. On the other hand, if the degree of polymerization (n) exceeds M2, the viscosity increases excessively, which may result in insufficient penetration into the porous matrix during the impregnation step of the PIP process.
[0058] In one embodiment, in a polyzirconium compound of Formula 1, a carboxyl group (-COO-) derived from acrylic acid can form a chelation bond with a zirconium atom. Chelation is a phenomenon in which a single ligand binds to a central metal through two or more coordination sites, and is thermodynamically more stable than a simple coordination bond. The chelation effect of the carboxyl group can play a key role in ensuring liquid-phase stability by suppressing excessive hydrolysis and condensation reactions of zirconium alkoxide.
[0059] In one embodiment, the polyzirconium compound of Formula 1 may include a vinyl group (-CH=CH2) derived from acrylic acid. The vinyl group has a carbon-carbon double bond, which can act as a reaction site for radical polymerization. Therefore, in the case of the polyzirconium compound, in the presence of a radical initiator (e.g., AIBN), the vinyl group forms a cross-link through a chain polymerization reaction, which is a key component of the double-crosslinking mechanism of the present invention.
[0060] In one embodiment, the polyzirconium compound remains in a liquid state at room temperature of about 20 to 25°C. This is an essential characteristic for the impregnation step of the PIP process, as the solid precursor cannot penetrate into the porous matrix. In one embodiment, the viscosity of the polyzirconium compound at 25°C may be in the range of about 100 cP to 1,000 cP. If the viscosity is less than 100 cP, the fluidity of the precursor is excessively high, which may cause leakage from the pores before curing after impregnation, or excessive shrinkage after curing may occur, leading to the formation of cracks. On the other hand, if the viscosity exceeds 1,000 cP, penetration into the micropores of the porous matrix is insufficient, resulting in the formation of a non-uniform microstructure, and additional processes such as vacuum impregnation may be required. For example, the viscosity of the polyzirconium compound at 25°C may be in the range of about 300 cP to 800 cP, about 470 cP to 570 cP, or about 500 cP to 540 cP. The viscosity range optimized for the PIP process may vary depending on the pore size, porosity, connectivity, etc. of the base material, but it is generally known that a range of about 300 to 800 cP is applicable to most UHTC base materials.
[0061] In one embodiment, the polyzirconium compound may have a ceramic yield of about 40% or more when heat-treated at 1300°C. For example, more preferably, the polyzirconium compound may have a ceramic yield in the range of about 45% to 60%, about 50% to 55%, or about 51% to 54% when heat-treated at 1300°C. The ceramic yield is defined as the percentage of the mass remaining after the precursor is thermally decomposed and converted into the final ceramic, and is one of the most important indicators determining the efficiency of the PIP process. The higher the ceramic yield, the fewer the number of repeated impregnations, thereby reducing process time and costs. Conventional zirconia precursors mostly exhibit a ceramic yield of 30 to 45%, which is due to significant mass loss caused by the decomposition and volatilization of chelating agents and organic components during the curing and thermal decomposition processes. On the other hand, the polyzirconium compound of the present invention can achieve a high ceramic yield of about 50% or more by maximizing the crosslinking density through a double crosslinking mechanism and enabling curing at a relatively low temperature (80°C) to suppress early decomposition.
[0062] In one embodiment, the polyzirconium compound can implement a dual crosslinking mechanism. For example, the polyzirconium compound can form a three-dimensional crosslinked network by simultaneously or sequentially inducing a condensation reaction between hydroxyl groups and a radical polymerization reaction between vinyl groups. In one embodiment, in the polyzirconium compound of Formula 1, the hydroxyl group (-OH) bonded to the zirconium atom can form a Zr-O-Zr bond through a condensation reaction with an adjacent molecule's hydroxyl group or alkoxide group. This condensation reaction is a traditional curing mechanism of the zirconium precursor and can form a linear or branched polymer structure. Additionally, in the polyzirconium compound of Formula 1, the vinyl group (-CH=CH2) derived from acrylic acid can form carbon-carbon bonds through a radical chain polymerization reaction in the presence of a radical initiator. As the radical initiator, thermal decomposition type initiators such as azobisisobutyronitrile (AIBN) and benzoyl peroxide (BPO) may be used without limitation. In one embodiment, the AIBN may be thermally decomposed at approximately 70 to 80°C to generate radicals, and the generated radicals attack the double bonds of vinyl groups to form new radicals, and as this chain reaction continues, a polymer network may be formed. Since the radical polymerization of the vinyl groups proceeds independently of the condensation reaction of the hydroxyl groups, the crosslinking density can be maximized by inducing the two reactions simultaneously or sequentially. In particular, since radical polymerization proceeds effectively at a relatively low temperature of approximately 70 to 80°C, the premature decomposition of the precursor that occurs during high-temperature curing can be suppressed.
[0063] According to the zirconium-based ceramic precursor material of the present invention, the density of crosslinking points in the three-dimensional network is increased through two independent reaction pathways, which can improve the ceramic yield by suppressing the collapse of the polymer structure during thermal decomposition. Furthermore, since the radical polymerization of the vinyl groups proceeds effectively at a low temperature of about 70 to 80°C, the early decomposition and volatilization of the precursor can be suppressed compared to conventional technology that requires high-temperature curing of 180°C or higher.
[0064] In addition, by controlling the relative rates of the condensation reaction and the radical polymerization, the curing time, shrinkage rate, residual stress, etc., can be optimized, and the high crosslinking density improves the mechanical strength and elastic modulus of the cured precursor, thereby suppressing crack formation during the pyrolysis process.
[0066] Method for manufacturing zirconium-based ceramic precursor materials
[0067] A method for manufacturing a zirconium-based ceramic precursor material according to an embodiment of the present invention may include: a first step of producing an intermediate product of formula b through a hydrolysis reaction between a zirconium alkoxide compound of formula a and acrylic acid according to the following reaction scheme 1; and a second step of synthesizing a polyzirconium compound of formula 1 through a condensation reaction of the intermediate products.
[0068] [Reaction Equation 1]
[0069]
[0070] In the above reaction scheme 1, R is a straight-chain or branched alkyl group having about 2 to 4 carbon atoms, and n is an integer from about 1 to 1000.
[0071] The zirconium alkoxide compound of the above chemical formula a has the chemical formula Zr(OR)4, where R can be a straight-chain or branched alkyl group having about 1 to 6 carbon atoms. The above zirconium alkoxide compound is a starting material for a sol-gel reaction, has a structure in which a zirconium atom is bonded to four alkoxide groups, reacts with water or alcohol to hydrolyze, and the resulting hydroxyl groups form a Zr-O-Zr bond through a condensation reaction.
[0072] In one embodiment, the zirconium alkoxide compound may be selected from the group consisting of zirconium ethoxide (Zr(OC2H5)4), zirconium n-propoxide (Zr(OC3H7)4), zirconium isopropoxide (Zr(Oi-C3H7)4), zirconium n-butoxide (Zr(OC4H9)4), etc. For example, the zirconium alkoxide compound may include zirconium propoxide, and preferably may be zirconium n-propoxide. The zirconium n-propoxide has the advantage of having appropriate reactivity and solubility and being commercially readily available.
[0073] The above acrylic acid (CH2=CH-COOH) is an unsaturated organic acid having both a carboxyl group and a vinyl group. The above acrylic acid can function as an acid catalyst, a chelating agent, and a crosslinking agent. Specifically, the carboxyl group of the above acrylic acid is acidic (pKa 4.25) and acts as an acid catalyst that promotes the hydrolysis reaction of the zirconium alkoxide. Accordingly, there is no need to add a separate acid catalyst (e.g., hydrochloric acid, nitric acid). In addition, the carboxyl group of the acrylic acid can control reactivity by forming a chelation bond with a zirconium atom. Through this chelation, the excessive condensation reaction of the zirconium alkoxide is suppressed, thereby preventing premature gelation and ensuring the stability of the liquid precursor. Furthermore, the vinyl group of the acrylic acid can act as a reaction site for a chain polymerization reaction in the presence of a radical initiator, and through the polymerization of the vinyl group, the crosslinking density can be maximized and the ceramic yield improved.
[0074] In one embodiment, the zirconium alkoxide compound and the acrylic acid may react in a molar ratio of about 1:1.5 to 1:2.5. The reaction molar ratio of the zirconium alkoxide compound and the acrylic acid may have a decisive influence on the physical properties of the synthesized polyzirconium compound. Specifically, if the reaction molar ratio of the zirconium alkoxide compound and the acrylic acid is less than 1:1.5, the amount of acrylic acid is insufficient, so its role as an acid catalyst is insufficient, causing the hydrolysis reaction to proceed slowly; the chelation effect is insufficient, leading to premature gelation or reduced liquid phase stability; and the low vinyl group content may result in a reduced crosslinking effect through radical polymerization. On the other hand, if the reaction molar ratio of the zirconium alkoxide compound and the acrylic acid exceeds 1:2.5, the excess of acrylic acid may lead to excessive chelation, which excessively inhibits the condensation reaction and may result in the formation of low molecular weight oligomers; and unreacted acrylic acid may remain even after curing, leading to a decrease in ceramic yield. In one embodiment, the zirconium alkoxide compound and the acrylic acid may react in a molar ratio of about 1:1.8 to 1:2.2 or about 1:2.0. In this case, liquid phase stability is improved, an oligomer of appropriate molecular weight is formed, and a precursor having a high ceramic yield can be obtained.
[0075] In one embodiment, the hydrolysis reaction of the first step may be carried out at room temperature of about 15 to 30°C or about 20 to 25°C. If the hydrolysis reaction temperature is below 15°C, the reaction rate becomes too slow and impractical, and if it exceeds 30°C, the hydrolysis and condensation reactions proceed too quickly and premature gelation may occur.
[0076] In one embodiment, the hydrolysis reaction of the first step may be carried out for about 6 to 48 hours. If the reaction time is less than 6 hours, the hydrolysis and chelation reactions are incomplete, making it difficult to obtain a uniform precursor, and if it exceeds 48 hours, viscosity may increase or gelation may occur due to excessive condensation reactions. In one embodiment, the hydrolysis reaction of the first step may be carried out for about 12 to 36 hours or about 20 to 28 hours.
[0077] In one embodiment, the hydrolysis reaction of the first step may be carried out under conditions where the reaction mixture is stirred for uniform mixing. In this case, the stirring speed may be in the range of about 100 to 1,000 rpm, and more preferably may be about 300 to 700 rpm or about 400 to 600 rpm.
[0078] In one embodiment, the hydrolysis reaction of the first step may be carried out under an inert atmosphere (e.g., argon, nitrogen). Reaction in the inert atmosphere can suppress side reactions caused by oxygen and moisture and prevent spontaneous polymerization of acrylic acid. However, the hydrolysis reaction of the first step may also be carried out in an air atmosphere under conditions that minimize moisture ingress.
[0079] In one embodiment, the zirconium alkoxide compound and the acrylic acid can be reacted by directly mixing them without a solvent. This has the advantage of simplifying the process and eliminating the solvent removal step. However, the reaction between the zirconium alkoxide compound and the acrylic acid may also be carried out in the presence of a solvent such as an alcohol (e.g., ethanol, 1-propanol, 2-propanol, 1-butanol), an ether (e.g., tetrahydrofuran, diethyl ether), or a ketone (e.g., acetone, methyl ethyl ketone).
[0080] In one embodiment, in the first step, an intermediate product may be synthesized having a structure in which some of the alkoxide groups of the zirconium alkoxide compound react with the acrylic acid to be substituted with an acrylic acid-derived ligand, some are hydrolyzed and converted into hydroxyl groups, and the remaining parts remain in an unreacted state. At this time, the carboxyl group of the acrylic acid may not simply be bonded to a single oxygen atom, but may form a chelation bond to the zirconium atom through two oxygen atoms (carbonyl oxygen and hydroxyl oxygen), and such a chelation structure is thermodynamically much more stable than a simple ester bond.
[0081] In one embodiment, the intermediate product of the formula b may have a structure comprising a residual alkoxide group, an acrylic acid-derived chelate ligand, and a hydroxyl group on a zirconium atom.
[0082] In the second step above, the intermediate products may undergo polymerization by forming Zr-O-Zr bonds through a condensation reaction. The condensation reaction may proceed spontaneously during the reaction of the first step, and the molecular weight may gradually increase as the reaction time elapses; furthermore, the condensation reaction may be accelerated by increasing the reaction temperature or extending the reaction time.
[0083] In one embodiment, the synthesized polyzirconium compound of Formula 1 may have an oligomer or polymer structure connected by Zr-O-Zr bonds, and each zirconium atom may have a complex coordination environment including a residual alkoxide group, a chelate ligand derived from acrylic acid (including a carboxyl group and a vinyl group), a hydroxyl group, and a Zr-O-Zr cross-link.
[0084] In one embodiment, after the second step, a post-treatment step may be performed to remove unreacted raw materials, by-products (water, alcohol), and residual solvent. The post-treatment may be performed through methods such as vacuum distillation, heat drying, and nitrogen bubbling.
[0085] In one embodiment, after the second step, volatile components can be removed by heating the reaction mixture at a temperature of about 50 to 100°C, about 60 to 80°C, or about 70 to 80°C for about 0.5 to 5 hours, about 1 to 3 hours, or about 1.5 to 2.5 hours. In this case, volatile components can be removed more efficiently by applying reduced pressure conditions (e.g., 10 to 100 mmHg).
[0086] After the above post-processing, the final product is obtained in the form of a yellow, viscous liquid, which is preferably stored in a sealed container to minimize contact with moisture and oxygen.
[0088] Method for manufacturing a composite ceramic molded body
[0089] A method for manufacturing a composite ceramic molded body according to one embodiment of the present invention may include: a first step of preparing a porous ceramic molded body; a second step of infiltrating a polyzirconium compound of the following chemical formula 1 and a radical initiator into the pores of the ceramic molded body; a third step of crosslinking the polyzirconium compound through polymerization between vinyl groups using the radical initiator; and a fourth step of converting the crosslinked polyzirconium compound into zirconium oxide by thermal decomposition.
[0090] [Chemical Formula 1]
[0091]
[0092] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 2 to 4 carbon atoms, and n is an integer from about 1 to 1000.
[0093] In the first step above, a porous ceramic molded body to be used as a matrix for the PIP process is prepared.
[0094] In one embodiment, the ceramic molded body may be formed from an ultra-high temperature ceramic (UHTC) material. For example, the ceramic molded body may be formed from a material selected from the group consisting of ZrB2 (zirconium diboride), ZrC (zirconium carbide), HfB2 (hafnium diboride), HfC (hafnium carbide), TaC (tantalum carbide), NbC (niobium carbide), and combinations thereof. In one embodiment, the ceramic molded body may be formed from ZrB2, ZrC, or HfC. For example, the ceramic molded body may be formed from ZrB2.
[0095] In one embodiment, the ceramic molded body may be composed of a single phase or be a composite material comprising a plurality of phases. For example, the ceramic molded body may be a composite material such as ZrB2-SiC, ZrC-SiC, HfC-TaC, etc.
[0096] In one embodiment, the shape of the ceramic molded body is not particularly limited and can have various shapes such as pellets, discs, rods, plates, and complex three-dimensional shapes.
[0097] In one embodiment, the porosity of the ceramic molded body may be in the range of about 20% to 70%. If the porosity is less than 20%, the penetration amount of the precursor is limited and the densification effect is negligible, and if it exceeds 70%, the mechanical strength of the molded body is excessively low, making it difficult to handle and potentially causing deformation or breakage during thermal decomposition. For example, the porosity of the ceramic molded body may be in the range of about 30% to 60% or about 40% to 55%.
[0098] In one embodiment, the average pore size of the ceramic molded body may be in the range of about 0.1 μm to 100 μm. If the pore size is less than 0.1 μm, penetration of the precursor is difficult, and if it exceeds 100 μm, the microstructure of the final composite may become non-uniform. For example, the average pore size of the ceramic molded body may be in the range of about 0.5 μm to 50 μm or about 1 μm to 20 μm.
[0099] In one embodiment, the method for manufacturing the porous ceramic molded body is not particularly limited, and known methods may be applied without limitation. For example, the porous ceramic molded body may be manufactured by various methods such as powder sintering, slurry casting, gel casting, and 3D printing.
[0100] In the second step above, a precursor composition comprising a polyzirconium compound of Formula 1 and a radical initiator can be infiltrated into the pores of the ceramic molded body.
[0101] In one embodiment, the precursor composition can be prepared by adding a radical initiator to a polyzirconium compound of Formula 1 and mixing them uniformly. That is, the radical initiator can be directly dissolved in the polyzirconium compound. Alternatively, the radical initiator may be first dissolved in a small amount of solvent (e.g., methylene chloride, acetone, tetrahydrofuran) and then mixed with the polyzirconium compound.
[0102] In one embodiment, the radical initiator may serve to initiate radical polymerization of vinyl groups in a subsequent curing step. A pyrolytic radical initiator may be used as the radical initiator, and specifically, may include azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), dicumyl peroxide (DCP), di-tert-butyl peroxide (DTBP), etc. For example, the radical initiator may be AIBN. The AIBN pyrolytically decomposes at 70 to 80°C to efficiently generate radicals and releases only nitrogen gas as a byproduct, thereby minimizing the impact on the ceramic yield. The amount of the radical initiator may be about 0.5 to 10 wt% relative to the mass of the polyzirconium compound. If the amount of the radical initiator is less than 0.5 wt%, radical polymerization may be incomplete and the effect of double crosslinking may be reduced, and if it exceeds 10 wt%, a rapid exothermic reaction may occur or non-uniform crosslinking may be formed due to the excessive radical concentration. For example, the amount of the radical initiator may be about 1 to 7 wt% or about 2 to 5 wt%.
[0103] In one embodiment, the precursor composition can be infiltrated into the pores of the ceramic molded body through various methods. In one embodiment, the ceramic molded body can be immersed in the precursor composition and left for a certain period of time (e.g., 1 to 24 hours) to infiltrate the precursor composition into the pores of the ceramic molded body by capillary action. In another embodiment, the ceramic molded body can be placed in a container together with the precursor composition, and a vacuum (10⁻¹ to 10⁻³ atm) can be applied to remove air from the pores, and then the pressure can be returned to atmospheric pressure to infiltrate the precursor composition into the pores of the ceramic molded body. In yet another embodiment, the ceramic molded body can be placed in a container together with the precursor composition, and a vacuum (10 -1 ~10 -3The precursor composition can be infiltrated into the pores of the ceramic molded body by applying an inert gas (e.g., argon, nitrogen) at high pressure (e.g., 2 to 10 bar) in combination with or alone of atm conditions. In another embodiment, the precursor composition can be infiltrated into the pores of the ceramic molded body using centrifugal force.
[0104] In one embodiment, a method combining vacuum impregnation and pressure impregnation sequentially may be used to infiltrate the precursor composition into the pores of the ceramic molded body. This two-stage impregnation process effectively removes air within the pores and maximizes the infiltration of the precursor, thereby securing a uniform microstructure.
[0105] In one embodiment, the penetration of the precursor composition into the pores of the ceramic molded body can be performed at room temperature (20 to 25 ℃) or at a slightly increased temperature (30 to 50 ℃). Raising the temperature slightly reduces the viscosity of the precursor, making penetration easier, but raising the temperature excessively can cause premature curing.
[0106] In the third step above, the polyzirconium compound can be crosslinked through polymerization between vinyl groups using the radical initiator.
[0107] In one embodiment, curing by crosslinking of the polyzirconium compound may be performed at a temperature above the thermal decomposition temperature of the radical initiator. For example, when AIBN is used as an initiator, the curing temperature may be in the range of 70 to 100°C. If the curing temperature is below 70°C, the thermal decomposition of the radical initiator proceeds slowly, which may result in an excessively long curing time or incomplete curing. On the other hand, if it exceeds 100°C, excessive heat may be generated due to rapid radical polymerization, or the thermal decomposition of the precursor may begin prematurely. For example, the curing temperature may be in the range of approximately 75 to 90°C. Furthermore, the curing time may be in the range of approximately 3 to 24 hours. If the curing time is less than 3 hours, the crosslinking reaction is incomplete, resulting in low mechanical strength and potential cracking during subsequent thermal decomposition. Conversely, curing exceeding 24 hours may result in a negligible effect on improving additional crosslinking density and may reduce process efficiency. For example, the curing time may be about 6 to 18 hours or about 10 to 14 hours.
[0108] In one embodiment, the curing of the polyzirconium compound may be performed in an inert atmosphere (e.g., argon, nitrogen) or an air atmosphere. An inert atmosphere can enable more efficient crosslinking by suppressing radical annihilation reactions caused by oxygen. Preferably, the curing may be performed in an argon atmosphere.
[0109] In one embodiment, when the polyzirconium compound is cured, the hydroxyl group condensation reaction and the vinyl group radical polymerization reaction may proceed simultaneously or sequentially. Since the hydroxyl group condensation reaction and the vinyl group radical polymerization reaction proceed independently of each other, the total crosslinking density can be maximized, and a high crosslinking density improves the mechanical strength of the cured precursor and suppresses the collapse of the polymer structure during thermal decomposition, thereby significantly improving the ceramic yield. When the curing of the polyzirconium compound is completed, the liquid polyzirconium compound is converted into a solid state.
[0110] In the above fourth step, the hardened polyzirconium compound can be converted into zirconium oxide by thermal decomposition.
[0111] In one embodiment, when the hardened polyzirconium compound is pyrolyzed in a temperature range of about 500 to 600°C, the organic components are decomposed and nano-sized t-ZrO2 is formed. This temperature range is suitable for initial ceramicization and allows for obtaining the finest crystal grains. In another embodiment, when the hardened polyzirconium compound is pyrolyzed in a temperature range of about 600 to 800°C, crystal grain growth of t-ZrO2 and a gradual phase transition to m-ZrO2 occur, allowing for the acquisition of a mixed phase of t-ZrO2 and m-ZrO2. In yet another embodiment, when the hardened polyzirconium compound is pyrolyzed in a temperature range of about 800 to 1,300°C, a complete phase transition to m-ZrO2 and crystal grain growth occur, allowing for the acquisition of larger crystal grains and an almost pure m-ZrO2 phase.
[0112] In one embodiment, the thermal decomposition temperature of the hardened polyzirconium compound can be selected according to the desired crystal structure, grain size, and phase ratio. For example, to obtain a mixed phase of t-ZrO2 and m-ZrO2 or a pure m-ZrO2 phase, the thermal decomposition of the hardened polyzirconium compound can be performed in a range of about 550 to 1,400 °C or about 600 to 1,300 °C. Meanwhile, if the ceramic molded body is formed of a boride such as ZrB2, the boride may form B2O3 in a high-temperature oxidizing environment, thereby accelerating oxidation; therefore, the thermal decomposition of the hardened polyzirconium compound can be performed in a temperature range of about 550 to 600 °C.
[0113] In one embodiment, the heating rate to the pyrolysis temperature may be in the range of about 1 to 50 ℃ / min. If the heating rate is excessively fast, exceeding 50 ℃ / min, excessive gas release may occur due to rapid pyrolysis, which may result in cracking or delamination. On the other hand, if the heating rate is excessively slow, less than 1 ℃ / min, it is impractical as it excessively increases the process time. For example, the heating rate to the pyrolysis temperature may be in the range of about 3 to 20 ℃ / min or about 5 to 10 ℃ / min.
[0114] In one embodiment, to pyrolyze the hardened polyzirconium compound, the holding time at the maximum pyrolysis temperature may be in the range of about 0.5 to 10 hours. If the holding time at the maximum temperature is less than 0.5 hours, the pyrolysis may be incomplete and residual carbon may remain, and if it exceeds 10 hours, excessive grain growth may occur. For example, the holding time at the maximum pyrolysis temperature may be in the range of about 1 to 6 hours or about 2 to 5 hours.
[0115] In one embodiment, the thermal decomposition process of the hardened polyzirconium compound can be carried out in various atmospheres such as air, oxygen, inert gas (argon, nitrogen), and vacuum.
[0116] In one embodiment, when the pyrolysis is performed in an air or oxygen atmosphere, the oxidative decomposition of organic components proceeds efficiently and complete conversion to ZrO2 is possible, but oxidation of the UHTC base may occur during high-temperature pyrolysis. In another embodiment, when the pyrolysis is performed in an inert gas atmosphere, oxidation of the base can be minimized, but the decomposition of organic components proceeds slowly and residual carbon may remain. In yet another embodiment, when the pyrolysis is performed in a vacuum atmosphere, oxidation of the base can be prevented and efficient removal of by-products is possible.
[0117] In one embodiment, to perform an efficient PIP process, most organic components are first removed by pyrolysis in an air atmosphere and a relatively low temperature region to produce ZrO2, and then, if necessary, a relatively high temperature heat treatment is additionally performed in an inert atmosphere or under vacuum to achieve grain growth and densification.
[0118] In one embodiment, after the completion of the pyrolysis, the manufactured composite ceramic molded body may be naturally cooled in a furnace or cooled at a controlled rate. Since rapid cooling can cause cracks due to thermal stress, the manufactured composite ceramic molded body after pyrolysis may be cooled at a rate of about 5 to 50 ℃ / min.
[0119] In one embodiment, the method for manufacturing a composite ceramic molded body of the present invention may repeatedly perform a cycle consisting of steps 2 through 4 until a desired density is achieved. During each cycle, the density of the manufactured composite ceramic molded body may gradually increase as the precursor composition penetrates into the remaining pores and is pyrolyzed to be converted into ZrO2. In one embodiment, the method for manufacturing a composite ceramic molded body of the present invention may repeat the cycle consisting of steps 2 through 4 about 1 to 10 times, about 2 to 7 times, or about 3 to 5 times. Since the polyzirconium compound of the present invention has a high ceramic yield, the number of cycle repetitions can be significantly reduced compared to the case where a conventional ceramic precursor is applied.
[0120] A composite ceramic molded body manufactured according to the manufacturing method of the present invention may be a composite material comprising a UHTC matrix material and a second phase of ZrO2. The second phase of ZrO2 may be uniformly dispersed in the pores and grain boundaries of the UHTC matrix as nano to micro-sized particles. The relative density of the manufactured composite ceramic molded body may be about 60% or more, and may be about 90% or more.
[0122] Specific embodiments of the present invention are described in detail below. However, the following embodiments are merely partial embodiments of the present invention, and the scope of the present invention is not limited to the following embodiments.
[0124] [Example 1]: Synthesis of PZC-12 Precursor
[0125] A magnetic stirrer was attached to a 200 mL three-necked flask maintained under an argon atmosphere, and 0.01 mol of Zirconium (IV) propoxide (approx. 3.27 g, based on a 70 wt% solution) was added. To this, 0.02 mol of acrylic acid (approx. 1.44 g) was slowly added dropwise. The reaction mixture was reacted for 24 hours under an argon atmosphere at room temperature (approx. 23 °C) while stirring at 500 rpm. Initially, the solution was clear yellow, but turbidity was observed after about 12 hours. After 24 hours, unreacted substances and residual solvent were removed by heating the reaction mixture to 75 °C and maintaining it for 2 hours.
[0126] Finally, about 3.8 g of PZC-12 precursor, a yellow viscous liquid, was obtained (yield: about 85%). The viscosity of the synthesized PZC-12 at 25°C was measured using a viscometer (Brookfield) equipped with a cone spindle, and it was confirmed to be about 518 cP.
[0128] [Comparative Example 1] Molar ratio 1:1 (PZC-11)
[0129] Under the same conditions as in Example 1, 0.01 mol of Zr(OPr)4 and 0.01 mol of acrylic acid (molar ratio 1:1) were reacted. As a result, a whitening phenomenon was observed during the reaction, but ultimately, a liquid precursor was not obtained and the mixture transitioned into a gel state. This is believed to be because the amount of acrylic acid was insufficient, resulting in a lack of chelation effect and premature gelation.
[0131] [Comparative Example 2] : Molecule 1:3 (PZC-13)
[0132] Under the same conditions as in Example 1, 0.01 mol of Zr(OPr)4 and 0.03 mol of acrylic acid (molar ratio 1:3) were reacted, and a yellow liquid precursor was obtained. However, when AIBN was added and curing was attempted at 80°C for 12 hours, it did not cure into a solid state but remained in a liquid state with slightly increased viscosity. This is believed to be because the excess acrylic acid excessively inhibited the condensation reaction, resulting in a lower molecular weight.
[0134] [Example 2] ZrO2 Preparation
[0135] A homogeneous solution was prepared by dissolving AIBN (0.15 g), a radical initiator, in methylene chloride (MC). 6 g of PZC-12 synthesized in Example 1 was added to this solution and thoroughly mixed. The mixture was transferred to an alumina crucible and heated at 80°C for 12 hours under an argon atmosphere to harden through a cross-linking reaction. The solid intermediate product obtained in this way was named c-PZC-12. The hardened bright yellow solid (c-PZC-12) was thermally decomposed in an oxidation furnace under an air atmosphere at temperatures of 500°C, 600°C, 700°C, 800°C, 1,000°C, and 1,300°C, respectively, to produce the final product, ZrO2. The white powders obtained at each pyrolysis temperature were named ZrO2-500, ZrO2-600, ZrO2-700, ZrO2-800, ZrO2-1000, and ZrO2-1300.
[0137] [Example 3] Preparation of ZrB2-ZrO2 Composite Using PIP
[0138] After drying a 50 vol% ZrB2 slurry, zirconium diboride (zrB2, ZrB2-F, d50: 2.12 μm, Japan New Metal Co., Osaka, Japan) pellets (diameter 10 mm) were prepared by heating at 1,900℃ for 1 h in a vacuum atmosphere (heating rate: 50 ℃ / min).
[0139] The manufactured ZrB2 pellets were placed in a graphite mold, and a PZC-12 precursor mixed with AIBN was poured over them to completely submerge the pellets. Subsequently, the graphite mold was placed in a metal container, and 10 -2 Vacuum infiltration was performed by evacuating under a vacuum of atm for 20 minutes. Subsequently, a high-pressure argon atmosphere of 5 bar was applied for 20 minutes to induce further infiltration of the precursor.
[0140] After the vacuum infiltration process, the specimen underwent a crosslinking reaction at 80°C for 12 h in an argon atmosphere, and then thermal decomposition was carried out at 600°C in air in a sintering furnace (heating rate: 5°C / min, maintained at 600°C for 4 h).
[0141] ZrB2-ZrO2 composite specimens were prepared by repeating the above process three times.
[0143] Table 1 below shows the ratio of reactants and the conditions for manufacturing ZrO2.
[0144] Role Sample Ratio of starting materials Crosslinking Temperature(°C) Pyrolysis Temperature(°C) Zr(OPr)4 AA Precursor PZC-11 1 1 - - PZC-12 1 2 - - PZC-13 1 3 - - Crosslinking precursor C-PZC-12 1 2 80 Fabricated Zirconia ZrO2-500 1 2 80 500 ZrO2-600 1 2 80 600 ZrO2-700 1 2 80 700 ZrO2-800 1 2 80 800 ZrO2-1000 1 2 80 1000 ZrO2-1300 1 2 80 1300
[0146] [Experimental Example 1] ZrO2 Precursor Synthesis Strategy and Characteristics
[0147] Figure 1 is a schematic diagram illustrating the entire manufacturing process including (a) synthesis of a ZrO2 precursor, (b) double crosslinking of the ZrO2 precursor, and (c) thermal decomposition of the cured ZrO2 precursor, and Figure 2 shows photographs of PZC samples before (a), after (b), and after (c) the reaction of Zr(OPr)4 and acrylic acid.
[0148] Referring to Figures 1 and 2, a sol-gel pathway using zirconium propoxide (Zr(OPr)4) and acrylic acid (AA) was adopted for the synthesis of PZC. Generally, zirconium alkoxides are highly reactive, making the use of a chelating agent essential to control unintended gelation. In this study, AA was selected as the chelating agent due to its three main advantages. First, the carboxyl group of AA controls reactivity through chelation with the Zr center, while the molecule's inherent acidity allows it to initiate the sol-gel reaction without a separate acid catalyst. Second, it possesses both a hydrophilic carboxyl group and a hydrophobic vinyl group, enhancing compatibility with the reactants. Finally, the vinyl group can be utilized as a reaction site for radical chain polymerization during the subsequent curing stage to maximize crosslinking density (see Figure 1).
[0149] To find the optimal precursor composition, the molar ratio of Zr(OPr)4 to AA was varied to 1:1 (PZC-11), 1:2 (PZC-12), and 1:3 (PZC-13), and the reactions were carried out at room temperature for 24 hours, after which their behavior was compared. At the beginning of the reaction, under all three conditions, Zr(OPr)4 was uniformly mixed with acrylic acid (AA) in the propanol solvent to form a transparent yellow solution [see Fig. 2(a)]. However, after 24 hours, a milky white phenomenon was observed only in the PZC-12 solution, confirming that gelation proceeded through a sol-gel reaction [see Fig. 2(b)]. Subsequently, vacuum distillation was performed at 75 °C for 1 h to remove reaction byproducts and solvent, resulting in PZC-11 and PZC-13 remaining in a solid phase, while PZC-12 was finally synthesized as a homogeneous yellow liquid precursor with fluidity [see Fig. 2 (c)].
[0150] These results are interpreted as being due to the fact that the balance between the two roles of AA—i) the role of an acid catalyst to initiate the reaction and ii) the role of a chelator to control reactivity—was decisively influenced by the molar ratio. In the case of PZC-11 (1:1), the amount of acid was insufficient to initiate the sol-gel reaction, so no significant polymerization occurred. On the other hand, in PZC-13 (1:3), although there was sufficient acid to initiate the reaction, it is believed that the excess AA coordinated to the Zr center and excessively blocked the reaction site, thereby inhibiting molecular growth sufficient to form a gel network. In contrast, under the condition of PZC-12 (1:2), it appears that a sufficient acid concentration was provided to initiate the reaction, while an appropriate level of chelation effect suppressed the excessive condensation reaction, resulting in the formation of a precursor in the form of a liquid-stable oligomer.
[0151] The viscosity of the synthesized PZC-12 was measured to be about 517.8 cP [see Figure 2 (c)], which is somewhat viscous but sufficient for application in the impregnation step of the PIP process.
[0152] The precursor designed in the present invention has the advantage of securing a high ceramic yield through a unique dual cross-linking mechanism during the curing stage. Conventional sol-gel precursors are cured solely through condensation reactions between hydroxyl groups (-OH); however, high temperatures of 180°C or higher are required to completely remove the chelating agent, and during this process, a portion of the precursor decomposes or volatilizes, causing mass loss. In contrast, the PZC-12 of the present invention induces radical chain polymerization between vinyl groups of AA via an AIBN initiator at a relatively low temperature of 80°C, in addition to the -OH group condensation reaction. This dual curing method plays a key role in significantly improving the final ceramic yield by maximizing the cross-linking density prior to ceramicization and effectively suppressing mass loss during the heating process.
[0154] [Experimental Example 2] Analysis of the molecular structure of PZC-12
[0155] FT-IR and NMR analyses were performed to elucidate the molecular structure and curing mechanism of the synthesized PZC-12 precursor. Figure 3 shows the FT-IR spectra of the reactant, the liquid precursor (PZC-12), and the cured precursor (c-PZC-12).
[0156] Referring to Figure 3, peaks attributable to CH stretching vibrations (2,920, 2,861 cm-1), CO stretching vibrations (1,121 cm-1), Zr-O bonds (646 cm-1), and Zr-OC bonds (1,548 cm-1) were commonly observed in the PZC-12 spectrum. Importantly, the C=O stretching vibration peak, which appeared at 1,764 cm-1 in pure acrylic acid (AA), was red-shifted to 1,728 cm-1 in PZC-12, which means that the carboxyl group of AA was successfully chelated to the Zr atom. This result clearly supports the fact that AA acted as a chelating agent that effectively inhibited the excessive sol-gel reaction of Zr(OPr)4.
[0157] Notable changes were observed in the spectrum of c-PZC-12 after curing. It was confirmed that the broad -OH peak (approx. 3,300 cm-1) and the C=C double bond peak of AA (1,644 cm-1) observed in PZC-12 had almost disappeared. This result demonstrates that the intended dual crosslinking mechanism was effectively realized, as both the condensation polymerization of the -OH group and the radical chain polymerization of the vinyl group proceeded successfully.
[0158] Figure 4 is for a more detailed analysis of the molecular structure of PZC-12 1 H and 13 Shows the C NMR analysis results.
[0159] Referring to Fig. 4, the vinyl proton peak of AA (5.5–6.8 ppm) was still distinctly observed in the PZC-12 1H-NMR spectrum [see Fig. 4(b)]. On the other hand, the -OH proton peak of the carboxylic acid, which appeared around 12 ppm in pure AA [see Fig. 4(a)], completely disappeared in PZC-12, clearly indicating that chelation bonds were formed rather than a simple mixture. Furthermore, it was confirmed that the propoxide group peak of the reactant Zr(OPr)4 (0.5–4.0 ppm) remained largely in the PZC-12 spectrum. This implies that the reactivity was appropriately controlled by the chelation effect of AA, ensuring that not all propoxide groups reacted and some remained. Along with this, a new peak of the terminal -OH group generated by the sol-gel reaction was observed around 4.2 ppm. This structure 13 This was further confirmed by the observation of peaks corresponding to the propoxide group (0-30, 65-75 ppm) in the C-NMR spectrum [see Figure 4 (c)].
[0161] [Experimental Example 3] Change in Crystal Structure of ZrO2 According to Temperature
[0162] Optimal pyrolysis conditions for producing ZrO2 from a PZC-12 precursor were established, and changes in crystal structure according to temperature were analyzed. Figure 5 shows photographs and XRD patterns of ZrO2 powders obtained by pyrolysis at different temperatures.
[0163] Referring to Fig. 5, ZrO2-500 prepared at 500 ℃ was dark gray due to residual carbon, whereas at temperatures above 600 ℃, a completely white powder was obtained. This suggests that the ceramicization of the precursor was incomplete under the 500 ℃ condition. These results are also clearly confirmed in the XRD patterns; ZrO2-500 shows a broad, blunt peak observed when the grain size is very small, whereas the samples prepared above 600 ℃ all show sharp crystallization peaks, indicating that most of it was converted to ZrO2 and that the ZrO2 grains grew with increasing temperature.
[0164] Detailed analysis of the XRD patterns revealed a distinct phase transformation depending on the pyrolysis temperature. ZrO2-500 synthesized at low temperatures exhibited a main peak (2θ) corresponding to the tetragonal (t-ZrO2) phase. 30.1°) appeared predominantly. However, as the sintering temperature increased, this peak gradually decreased, and the intrinsic peak of the monoclinic (m-ZrO2) phase (2θ) appeared. 28.2°, 31.5°) were strongly expressed. Finally, in ZrO2-1300 synthesized at 1,300 ℃, almost pure m-ZrO2 crystalline phase was observed.
[0165] To quantitatively analyze these phase changes and grain sizes, Rietveld analysis and the Scherrer equation were used, and the results are summarized in Table 2.
[0166] Sample Ratio of grain (%) Grain size by crystalline phase (nm) Average grain size (nm) t-ZrO2 m-ZrO2 t-ZrO2 m-ZrO2 ZrO2-500 70.4 29.6 9.9 8.1 9.37 ZrO2-600 49.13 50.87 11.5 16.4 13.99 ZrO2-700 31.38 68.62 16.9 22.5 20.74 ZrO2-800 13.31 86.69 19.3 29.9 28.49 ZrO2-1000 3.77 96.23 15.2 31.5 30.89 ZrO2-1300 0.84 99.16 22.8 74.5 74.07
[0167] Referring to Table 2, ZrO2-500 was composed of approximately 70.4% t-ZrO2 and 29.6% m-ZrO2. As the temperature increased, the t-ZrO2 fraction continuously decreased and the m-ZrO2 fraction increased, confirming that ZrO2-1300 was ultimately composed of m-ZrO2. The average grain size also started at 9.37 nm in ZrO2-500 and steadily increased due to grain growth as the temperature increased, reaching 74.07 nm in ZrO2-1300.
[0168] The most interesting aspect of these results is that t-ZrO2 is stabilized into a metastable phase at low temperatures. Generally, it is known that bulk ZrO2 is thermodynamically stable as m-ZrO2 at room temperature and undergoes a phase transition to t-ZrO2 only above 1,170 °C. However, in the nanoscale region, phase stability differs due to surface energy effects. That is, below a certain critical size, the surface energy of t-ZrO2 decreases while the surface energy of m-ZrO2 increases, allowing t-ZrO2 to exist stably even at room temperature. In this invention, the PZC-12 precursor, with its molecular weight controlled via AA, induces the formation of nanometer-sized fine crystal grains upon low-temperature pyrolysis. In fact, the average crystal grain sizes of ZrO2-500 and ZrO2-600 were 9.37 nm and 13.99 nm, respectively, confirming that they are sufficiently small to stabilize the t-ZrO2 crystal grains. Subsequently, as the sintering temperature increases, grain growth occurs, and when the grain size exceeds the critical size, ZrO2 undergoes a phase transition back to m-ZrO2, which is thermodynamically stable like the bulk state. Consequently, it was confirmed that the combination of initial nanograin formation through precursor design and grain growth via subsequent heat treatment is the key mechanism controlling the temperature-dependent crystal phase change of ZrO2.
[0170] [Experimental Example 4] Microstructure of ZrO2
[0171] Figure 6 shows images of the microstructure of ZrO2 powder as a function of pyrolysis temperature observed using SEM.
[0172] Referring to Figure 6, at low magnification of 5,000x, all samples exhibited an irregular agglomerate surface structure, and no significant differences in macroscopic morphology were found depending on the temperature. However, at high magnification of 200,000x, distinct changes in microstructure were confirmed. In the case of ZrO2-500, the boundaries between particles were indistinct, and the structure appeared to be covered with very fine nanoparticles in an amorphous phase. Consistent with the previous analysis results, this is attributed to the fact that at a low temperature of 500°C, ceramicization was incomplete, resulting in a mixture of nanocrystals, amorphous ceramics, and unreacted precursor materials. On the other hand, clear grains could be observed in samples of ZrO2-600 or higher, where complete ceramicization was achieved. In particular, as the pyrolysis temperature increased from 600°C to 1,300°C, a phenomenon was observed in which the particle size increased noticeably. The results of direct microstructural observation through SEM exactly match the grain size increase trend calculated using the Scherrer equation of the XRD pattern, clearly showing that grain growth occurred with increasing temperature.
[0174] [Experimental Example 5] Thermal properties and ceramicization behavior of PZC-12
[0175] TGA-DSC was performed to analyze the pyrolysis behavior, ceramicization process, and final yield of the synthesized PZC-12 precursor, and the results are shown in Figure 7. The analysis was carried out in an air atmosphere at a heating rate of 5°C per minute up to 1,300°C, similar to the actual pyrolysis process.
[0176] Referring to Fig. 7, the TGA curve can be broadly divided into three sections. In the first section (I, 30–250 °C), a mass loss of approximately 10% was observed, which is attributed to the volatilization of low molecular weight substances such as residual solvent, adsorbed moisture, and unreacted AA remaining in the precursor. In the second section (II, 250–530 °C), the main thermal decomposition of the precursor occurs. Decomposition of chelation bonds or organic ligands contained in the polymer chain begins at approximately 250 °C, and a rapid mass loss occurs starting at 300 °C. The most notable phenomenon in this section is the strong exothermic peak at 458 °C observed in the DSC curve. This peak corresponds to the crystallization process in which the amorphous zirconium oxide undergoes a phase transition to the crystalline t-ZrO2. This crystallization was found to be completed at approximately 522 °C, which clearly explains that the low pyrolysis temperature was the direct cause of the previous XRD and SEM analysis results, in which the ZrO2-500 sample pyrolyzed at 500 °C showed incomplete crystallinity. In the third section (III, 530–1,300 °C), thermal behavior stabilizes. The mass loss from 600 °C to 1,300 °C is only about 0.5%, indicating that most organic matter has been removed and converted into a stable oxide.
[0177] The final residue at 1,300 ℃ was 52.7%, which represents the ceramic yield of the PZC-12 precursor developed in this invention. To compare with the yields of other precursors, the ceramic yields of various ceramic precursors are presented in Table 3. To date, there have been almost no reported cases regarding liquid ZrO2 precursors directly applicable to the PIP process. Therefore, in this invention, relative performance was examined by comparing the yields with polymer-based precursors reported for other uses, rather than with the precursor developed for PIP.
[0178] Precusor Yield Pyrolysis Temperature ZC13 ~30% 1,200℃ YSZ precursor ~15% 800℃ PZCS-2 43.9% 900℃ PZSA 53.5% 1,375℃ BCZr-1100-air 58% 1,100℃
[0179] Referring to Table 3, the ceramic yield of the ZrO2 precursor developed in the present invention was relatively excellent. Since most generally reported precursors exist in a solid phase, a separate solvent must be added to undergo a dissolution process in order to utilize them in a liquid phase, and a substantial reduction in yield is inevitable during this process. On the other hand, the PZC-12 precursor of the present invention secured a high ceramic yield despite being a low-viscosity liquid phase that does not contain a solvent. This demonstrates that PZC-12 possesses both excellent process suitability and high conversion efficiency as a liquid ZrO2 precursor for PIP application.
[0180] Meanwhile, in the DSC curve of the high-temperature region, broad and gradual thermal changes are observed in the endothermic portion, which is attributed to complex microstructural changes such as grain growth at high temperatures and the accompanying phase transformation of ZrO2.
[0182] [Experimental Example 6] Preparation of ZrB2-ZrO2 Composite using PIP Process
[0183] To verify the feasibility of applying the synthesized PZC-12 precursor to actual processes, a PIP process-based ZrB2-ZrO2 composite was prepared using a porous ZrB2 molded body with a relative density of 55%. As shown in Fig. 8, the manufacturing process was performed by repeating a cycle of pyrolysis at 600 °C for 4 hours after PZC-12 impregnation a total of three times. Fig. 9 shows the density profile of the ZrB2-ZrO2 composite after each step of the PIP process (a), and the XRD patterns of the ZrB2-ZrO2 composite before PIP and after three cycles. The reason the pyrolysis temperature was set to 600 °C is that ceramicization of the precursor is incomplete below 500 °C, and excessive oxidation of the ZrB2 matrix is a concern at temperatures too high; therefore, it was determined to be the optimal condition to achieve complete crystallization while minimizing damage to the matrix.
[0184] Referring to Figures 8 and 9, a ZrB2-ZrO2 composite was successfully manufactured through three PIP processes, and it was confirmed that effective densification proceeded, with the density of the initial molded body increasing significantly from 3.43 g / cm3 to 3.77 g / cm3 [see Figure 9 (a)]. In addition, XRD analysis clearly confirmed that ZrO2 was successfully formed within the ZrB2 matrix after three PIP processes [see Figure 8 (b)]. Despite the ZrB2 molded body having a relatively high relative density (approx. 55%), the precursor synthesized in the present invention exhibited low viscosity, confirming that stable impregnation is possible without the addition of a solvent. Even when the PIP process was repeated only three times, the relative density of the composite reached approximately 63%, and it is judged that high-density ceramics with a relative density of over 80% can be manufactured by further increasing the number of PIP cycles. These results demonstrate that the PZC-12 precursor developed in the present invention possesses excellent processability as a ZrO2-based liquid precursor suitable for the PIP process, and prove that it is sufficiently possible to manufacture complex shapes and improve the density of binary ceramic composites by utilizing it.
[0185] One interesting point is the crystalline phase of ZrO2 formed within the composite. In the previous powder experiments, t-ZrO2 and m-ZrO2 were mixed in a ratio of approximately 5:5 upon pyrolysis at 600°C, but the ZrO2 formed within the ZrB2 matrix mostly existed in the m-ZrO2 phase. This is attributed to the ZrO2 generated by surface oxidation of the ZrB2 molded body within the ZrB2 matrix. It is believed that when ZrB2 is exposed to air, a thin layer of ZrO2 is formed due to surface oxidation even at room temperature, and this ZrO2 layer acts as a nucleus for the crystallization and grain growth of amorphous ZrO2 during precursor pyrolysis, thereby increasing the crystal size of the ZrO2 formed inside the preform compared to the pyrolysis of the pure precursor even during pyrolysis at 600°C. As a result, it is estimated that the grain size grew beyond the critical size that stabilizes the t-ZrO2 phase, and a phase transformation to thermodynamically stable m-ZrO2 occurred [see Fig. 9 (b)].
[0187] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art will understand that various modifications and changes can be made to the invention without departing from the spirit and scope of the invention as set forth in the following claims. Explanation of the symbols
[0188] doesn't exist
Claims
Claim 1 A zirconium-based ceramic precursor material comprising a polyzirconium compound having the chemical structure of the following chemical formula 1, which is in a liquid state at room temperature as a zirconium oxide precursor material: [Chemical Formula 1] In the above chemical formula 1, R is a straight-chain or branched alkyl group having 1 to 6 carbon atoms, and n is an integer from 1 to 1000. Claim 2 A zirconium-based ceramic precursor material according to claim 1, wherein the -OR is selected from the group consisting of an ethoxide group, an n-propoxide group, and an n-butoxide group. Claim 3 A zirconium-based ceramic precursor material according to claim 2, characterized in that the -OR is an n-propoxide group. Claim 4 A zirconium-based ceramic precursor material according to claim 1, characterized in that the viscosity of the polyzirconium compound at 25°C is about 470 to 570 cP. Claim 5 A zirconium-based ceramic precursor material according to claim 1, characterized in that, when heat-treated at 1300℃, the ceramic yield of the polyzirconium compound is 50 to 55%. Claim 6 A method for preparing a zirconium-based ceramic precursor material, comprising: a step of producing an intermediate product of formula b through a hydrolysis reaction between a zirconium alkoxide compound of formula a and acrylic acid according to the following reaction scheme 1; and a step of synthesizing a polyzirconium compound of formula 1 through a condensation reaction of said intermediate products; [Reaction Scheme 1] In the above reaction scheme 1, R is a straight-chain or branched alkyl group having 1 to 6 carbon atoms, and n is an integer from 1 to 1000. Claim 7 A method for manufacturing a zirconium-based ceramic precursor material according to claim 6, wherein in the above reaction formula 1, -OR is selected from the group consisting of an ethoxide group, an n-propoxide group, and an n-butoxide group. Claim 8 A method for manufacturing a zirconium-based ceramic precursor material according to claim 7, wherein the zirconium alkoxide compound comprises zirconium propoxide. Claim 9 A method for manufacturing a zirconium-based ceramic precursor material according to claim 6, characterized in that the zirconium alkoxide compound and the acrylic acid react in a molar ratio of 1:1.8 to 1:2.
2. Claim 10 A method for manufacturing a zirconium-based ceramic precursor material according to claim 9, wherein in the first step, some of the alkoxide groups of the zirconium alkoxide compound are substituted with a ligand derived from the acrylic acid, and some remain. Claim 11 A method for manufacturing a composite ceramic molded body, comprising: a first step of preparing a porous ceramic molded body; a second step of infiltrating a polyzirconium compound of the following chemical formula 1 and a radical initiator into the pores of the ceramic molded body; a third step of crosslinking the polyzirconium compound through polymerization between vinyl groups using the radical initiator; and a fourth step of converting the crosslinked polyzirconium compound into zirconium oxide by thermal decomposition; [Chemical Formula 1] In the above chemical formula 1, R is a straight-chain or branched alkyl group having 1 to 6 carbon atoms, and n is an integer from 1 to 1000. Claim 12 A method for manufacturing a composite ceramic molded body according to claim 11, wherein the ceramic molded body is formed of ZrB2, ZrC, or HfC. Claim 13 A method for manufacturing a composite ceramic molded body, characterized in that, in claim 12, the crosslinking of the polyzirconium compound is performed at 70 to 100°C. Claim 14 A method for manufacturing a composite ceramic molded body according to claim 12, characterized in that the thermal decomposition of the cross-linked polyzirconium compound is performed at a temperature of 550°C or higher and 1400°C or lower.